ONTOLOGI BARANG BUKTI: MENGEMBALIKAN MARWAH HUKUM DARI TONTONAN KE KEADILAN SUBSTANTIF - Elwindra Elwindra; Yudhi Hertanto (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT The phenomenon of displaying confiscated cash derived from corruption cases by law enforcement agencies in large amounts has become an increasingly prominent practice in the public communication of law enforcement in Indonesia. This practice raises an ontological question concerning the nature of confiscated money, namely whether it functions as an instrument for recovering state losses or merely as a symbolic representation of successful law enforcement. This study aims to examine the ontology of confiscated money and critically analyze the spectacle of law enforcement through the perspective of Guy Debord’s Society of the Spectacle and legalistic ethics. This study employs a normative-philosophical legal research method using philosophical and conceptual approaches and utilizes secondary data consisting of legislation, institutional reports, and scientific literature related to asset recovery. The findings reveal that confiscated money possesses material, juridical, and symbolic dimensions; however, the practice of visual exposure risks creating a legal spectacle that obscures the accountability of asset recovery. Therefore, strengthening evidence-tracking transparency, reforming asset governance, and accelerating the enactment of the Asset Forfeiture Bill are necessary to promote substantive justice and the restoration of public rights. ABSTRAK Fenomena ekspos uang sitaan hasil tindak pidana korupsi oleh aparat penegak hukum dalam jumlah besar telah menjadi praktik yang semakin menonjol dalam komunikasi publik penegakan hukum di Indonesia. Praktik ini memunculkan persoalan ontologis mengenai hakikat keberadaan uang sitaan, yakni apakah diposisikan sebagai instrumen pemulihan kerugian negara atau sekadar representasi simbolik keberhasilan penindakan hukum. Penelitian ini bertujuan membedah ontologi uang sitaan serta mengkritik praktik tontonan hukum melalui perspektif Society of the Spectacle Guy Debord dan etika legalistik. Penelitian menggunakan metode hukum normatif-filosofis dengan pendekatan filosofis dan konseptual serta memanfaatkan data sekunder berupa peraturan perundang-undangan, laporan kelembagaan, dan literatur ilmiah terkait pemulihan aset. Hasil penelitian menunjukkan bahwa uang sitaan memiliki dimensi material, yuridis, dan simbolis, namun praktik ekspos visual berpotensi membentuk spektakularisasi hukum yang mengaburkan akuntabilitas pemulihan aset. Oleh karena itu, penguatan transparansi alur barang bukti, reformasi tata kelola aset, dan percepatan pengesahan RUU Perampasan Aset diperlukan untuk mendorong keadilan substantif dan pemulihan hak publik.